Marketing communication : new approaches, technologies, and styles - Kimmel, Allan J. (Oxford University, 2009)
Focuses on the various developments in marketing communication, including advertising, public relations, and sales promotions. Written by twenty-five prominent contemporary marketing experts from the US and Europe, this book is useful for those interested in marketing techniques and communication technologies of the 21st Century